Optimized mass flux ratio of double-flow solar air heater with EHD - N. Kasayapanand (2018)
The numerical study of laminar forced convection inside double-flow solar air heater with electrohydrodynamic technique is investigated by finite difference method. The electric field is generated by the wire electrodes charged with DC high voltage. The mathematical modeling of computational fluid dynamics includes the interactions among electric field, flow field, and temperature field. It can be perceived that augmented heat transfer with presence of an electric field increases with the supplied voltage but decreases with the total mass flux. The optimized mass flux ratio is expressed incorporating with concerning parameter comprising of the electrode arrangement, the number of electrodes, the total heat flux at an absorbing plate, and the channel geometry. © 2006 Elsevier Ltd. All rights reserved.